2002
DOI: 10.1099/00221287-148-5-1533
|View full text |Cite
|
Sign up to set email alerts
|

The cell surface protein Ag43 facilitates phage infection of Escherichia coli in the presence of bile salts and carbohydrates

Abstract: It was found that infection of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 35 publications
2
27
0
1
Order By: Relevance
“…EPEC, an E. coli pathovar that is associated with infant diarrhea and the production of attaching and effacing lesions on enterocytes, also colonizes the small intestine (17,19). EPEC has been demonstrated in numerous studies to respond to bile salts by increasing adhesion to epithelial cells (25,35,48). de Jesus et al demonstrated that bile exposure enhanced the adhesion of typical EPEC strain E2348/69 to Hep2 epithelial cells between 1.3-and 2.6-fold.…”
Section: Pathogenic E Colimentioning
confidence: 99%
“…EPEC, an E. coli pathovar that is associated with infant diarrhea and the production of attaching and effacing lesions on enterocytes, also colonizes the small intestine (17,19). EPEC has been demonstrated in numerous studies to respond to bile salts by increasing adhesion to epithelial cells (25,35,48). de Jesus et al demonstrated that bile exposure enhanced the adhesion of typical EPEC strain E2348/69 to Hep2 epithelial cells between 1.3-and 2.6-fold.…”
Section: Pathogenic E Colimentioning
confidence: 99%
“…Dam is also required for phase variation of expression of the agn43 gene (also designated flu) in E. coli (72,116,126). This gene encodes the outer membrane protein Ag43, which causes autoaggregation, enhances biofilm formation, and may affect phage adsorption (64,100,269). The regulation of phase variation of Ag43 is quite different from that of pap and requires only the oxidative stress response protein OxyR in addition to Dam.…”
Section: Epigenetic Regulationmentioning
confidence: 99%
“…Recent investigations have demonstrated that the ability of Ag43 to mediate cell-cell interactions contributes to E. coli biofilm formation in minimal media (88), and microarray experiments have revealed that Ag43 expression was significantly higher within the biofilm than at any stage of planktonic growth (437). Interestingly, Ag43 was also demonstrated to facilitate , P1, and T4 phage infection of E. coli (150), raising the possibility that phage therapy could be used for certain E. coli-mediated diseases (526).…”
Section: Antigen 43mentioning
confidence: 99%